Analisis Kebutuhan Pengembangan E-Modul Interaktif Matematika Berbasis Budaya Lokal Kabupaten Batang - APRILIANI, YOLANDA; Nasution, Nur Baiti (Universitas Mercu Buana Yogyakarta, 2025)
The purpose of this study is to conduct a needs analysis for developing instructional materials used in schools, namely an interactive mathematics e-module based on local culture by integrating the local culture of Batang Regency for vocational high school (SMK) students. The method used in this study is qualitative, oriented towards product development in the form of an e-module. Data collection techniques included interviews with grade XI mathematics teachers and students, as well as distributing questionnaires to grade XI students at SMK N 1 Kandeman. The object of this research is the development analysis of an interactive e-module based on the local culture of Batang Regency for the topic of composition and inverse functions. The subjects of this study are grade XI students and a grade XI mathematics teacher at SMK N 1 Kandeman. Data collection methods in this study include curriculum analysis, material analysis, and field condition analysis based on the background of the local culture. Based on the results of the analysis, it was found that students genuinely need instructional materials in the form of an electronic-based module to assist them in understanding the material, improve their problem-solving skills in the topics of composition and inverse functions, and help them relate the learning process to the local culture in their environment.